The Impact of TV Violence on Violent Crime:Reanalyzing Meta-Analyses and Looking at Longitudinal Figures - Hetsroni, Amir (Mediální studia [Media Studies], 2013)
This article reviews studies on violent crime in television programmes and research documenting the impact of such content on criminal activities. The results of eight meta-analyses pertaining to the behavioural effects of the representation of violence in general and violent crime in particular in TV programming are reanalyzed and year-by-year figures concerning the share of crimerelated programming among the most often watched shows and the level of violent crime according to official statistics in America are juxtaposed. The study found no evidence that an increase in the share of crime-related programming predicts a similar increase in actual crime. In fact, the data even suggest that the effect of exposure to televised crime on criminal behaviour has been declining since the mid-1990s.
https://katalog.adlr.link/Record/ai-53-161207